Iowa RBA, December 8, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for December 8, 1997. Highlights of the update include sightings of a Varied Thrush, White-winged Crossbills, Common Redpolls, a Hoary Redpoll, a first year Thayer's Gull, and two Surf Scoters. Also included are handwritten notes for the next week's update with sightings of a Ross's Gull, a Clark's Grebe, and a Ringed Turtle-Dove as well as reports of numerous species of Sparrows. Epson - sheet feed/flatbed